An image encryption algorithm based on a compound-coupled chaotic system - Zhang, Hangming; Hu, Hanping (Digital signal processing, 2024)
Image encryption based on chaotic systems and DNA encoding is the focus of current research. However, existing image encryption algorithms lack attention with regard to the application efficiency of scrambling and diffusing operations based on DNA encoding and chaos, resulting in more redundancy and low efficiency. In practical applications, when chaotic systems are simulated on digital platforms, their chaotic performance will be weakened because of the presence of dynamic degradation. In addition, many chaotic systems have simple control parameters, making their behavior easily predictable. These flaws weaken the security and efficiency of cryptographic systems. For the purpose of solving the above problems, a new simultaneous confusion-diffusion image encryption algorithm (SCD-IEA) is presented that fully considers application efficiency and security. Firstly, a compound-coupled chaotic system (CCCS) is used to solve the problems listed above. Following that, a novel image encryption method is proposed using DNA coding and CCCS based on simple logistic and sine mappings. The algorithm improves application efficiency and performs synchronous scrambling diffusion encryption based on DNA coding. Simulation and security analysis results show that our SCD-IEA contributes to a higher level of security and superior performance than some representative methods.